Compliments and responses to compliments produced by brazilian learners of english - Morisawa, Sanae Jomori (2005)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente